THE MULTIMEDIA RESOURCES IN LANGUAGE TEACHING (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
Some highlights in the contribution of Multimedia resources in teaching and learning of English language are to be outlined and the ways the Multimedia can assist in English course planning are to be examined. Use of Multimedia resources is an essential subject matter in English language education that it is presented all through this paper. In this paper we come across more discussions of Multimedia related to the teaching English language skills. Multimedia-assisted learning environments in addition to content-specific applications of Multimedia in English language skills like Listening, Speaking, Reading and Writing are to be examined. This paper will also explore the Multimedia applications and the Internet, standards for Multimedia-language students, and teaching and learning with Multimedia. Moreover I endeavour to show some English teachers and students attitude towards use of Multimedia in English language teaching. Finally the conclusions are drawn by means of the review of literature indicated.